Comics and Stuff - Jenkins, Henry 1958-; Jenkins, Henry 1958- (Book collections on Project MUSE., 2020)
Comics are stuff; comics tell stories about stuff; and they display stuff.When we use the phrase "and stuff" in everyday speech, we often mean something vague, something like "etcetera." In this book, stuff refers not only to physical objects, but also to the emotions, sentimental attachments, and nostalgic longings that we express--or hold at bay--through our relationships with stuff.In Comics and Stuff, his first solo authored book in over a decade, pioneering media scholar Henry Jenkins moves through anthropology, material culture, literary criticism, and art history to resituate comics in the cultural landscape. Through over one hundred full-color illustrations, using close readings of contemporary graphic novels, Jenkins explores how comics depict stuff and exposes the central role that stuff plays in how we curate our identities, sustain memory, and make meaning. .